The black swan eaudiobook - Taleb, Nassim Nicholas (Incerto, 2007)
Maverick thinker Nassim Nicholas Taleb had an illustrious career on Wall Street before turning his focus to his black swan theory. Not all swans are white, and not all events-no matter what the experts think-are predictable. Taleb shows that black swans, like 9/11, cannot be foreseen and have an immeasurable impact on the world. "[Taleb] administers a severe thrashing to MBA- and Nobel Prize-credentialed experts who make their living from economic forecasting."-Booklist